Gambaran Derajat Keparahan Stroke Iskemik Berdasarkan Skor National Institute of Health Stroke Scale (NIHSS) di Ruang Rawat Inap Saraf RSUD Cut Meutia Aceh Utara - Maghfirah, Cut Zuhra; Ikhsan, Maulana; Fonna, Tischa Rahayu (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
Stroke is the leading cause of disability and the second leading cause of death worldwide, with ischemic stroke being the most common type. Assessing stroke severity is essential for determining prognosis and guiding patient management. This study aimed to describe the severity of ischemic stroke using the National Institute of Health Stroke Scale (NIHSS) score in patients at RSUD Cut Meutia Aceh Utara during the period of September to November 2024. This research employed a quantitative descriptive design with a cross-sectional approach. Data were obtained from medical records of ischemic stroke patients meeting the inclusion criteria. Stroke severity was assessed using the NIHSS score at two observation points: 24 hours and 3 days after hospital admission. Data analysis was conducted using frequency distribution and percentage methods. The results showed that among the 77 ischemic stroke patients studied, the majority were in the productive age group (15–65 years), accounting for 72.7% of cases, and males were more affected (63.6%) than females (36.4%). The main risk factors were hypertension (84.4%), followed by smoking (39%) and diabetes mellitus (36.4%). The NIHSS assessment after 24 hours revealed that most patients experienced severe stroke (64.9%). However, after 3 days, improvement was observed, with the majority experiencing moderate stroke (84.4%). Age, gender, and the number of risk factors significantly influenced the severity and recovery of stroke patients.